Green Therapy: Upaya Pencegahan Burnout pada Mahasiswa Agribisnis Melalui Aktivitas Alam - Ritonga, Ristra Sandra; Sandi, Mei Ryan (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2025)
Academic burnout is a common psychological condition experienced by students, especially in study programs with high practical workloads such as Agribusiness. This study aims to examine the effectiveness of green therapy as an effort to prevent burnout through nature activities. Using a descriptive qualitative approach, the intervention was carried out for four weeks on 12 Agribusiness students who showed symptoms of burnout based on the Maslach Burnout Inventory–Student Survey (MBI-SS) scale. Green therapy activities include soil cultivation, planting, plant care, self-reflection, and symbolic harvesting. The results showed a significant decrease in the three main indicators of burnout, namely emotional exhaustion, cynicism, and low academic efficacy. The average burnout score decreased from 4.2 to 2.8 after the intervention. In-depth interviews also revealed that gardening activities increased calmness, a sense of connectedness to nature, and self-awareness of participants. Green therapy has been proven to be an effective natural method in reducing academic burnout and is worthy of being integrated into practice-based learning activities in agribusiness higher education.